Osteonecrosis of jaw bones: A complication of severe dengue - S M Ravi Prakash; Aarfa Nasim; Nagaraju Kamarthi; Swati Gupta (Wolters Kluwer Medknow Publications, 2018)
Dengue fever is an acute infection of viral origin caused by female Aedes aegypti mosquito. It has a flu-like illness that can be fatal if left untreated. Several systemic complications such as hypovolemia and circulatory shock with organ failure, oral complications such as post-extraction bleeding, and candidiasis have been reported. Rare complications such as lock jaw and osteonecrosis can also manifest in severe form of dengue fever. Very scanty literature exists to document this association. This case report is an evidence to document and emphasize that these complications develop in severe cases of dengue fever even without any preexisting odontogenic or periodontal etiology.